2007
DOI: 10.1086/509941
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Cost of Separate Genders Revealed by Male‐Limited Evolution

Abstract: Theory predicts that intralocus sexual conflict can constrain the evolution of sexual dimorphism, preventing each sex from independently maximizing its fitness. To test this idea, we limited genome-wide gene expression to males in four replicate Drosophila melanogaster populations, removing female-specific selection. Over 25 generations, male fitness increased markedly, as sexually dimorphic traits evolved in the male direction. When male-evolved genomes were expressed in females, their fitness displayed a nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
186
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(207 citation statements)
references
References 34 publications
14
186
7
Order By: Relevance
“…Artificial selection for increased investment in a specific sex function would constitute a direct test of the lability of hermaphroditism and of levels of standing sexually antagonistic genetic variation. Such an approach has also been suggested by Schärer [34], and experimental evolution has been successful in detecting intra-locus sexual conflict in laboratory populations of Drosophila melanogaster [13,75,76]. Colour has occasionally been used as a marker trait in experimental evolution studies (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
“…Artificial selection for increased investment in a specific sex function would constitute a direct test of the lability of hermaphroditism and of levels of standing sexually antagonistic genetic variation. Such an approach has also been suggested by Schärer [34], and experimental evolution has been successful in detecting intra-locus sexual conflict in laboratory populations of Drosophila melanogaster [13,75,76]. Colour has occasionally been used as a marker trait in experimental evolution studies (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although recent studies have demonstrated standing genetic variation in sexually antagonistic loci within populations in diverse taxa Fedorka & Mousseau 2004;Pischedda & Chippindale 2006;Brommer et al 2007;Foerster et al 2007;Prasad et al 2007;Bilde et al 2009;Delcourt et al 2009), the impact of ISC on population-level processes remains unexplored (Bonduriansky & Chenoweth 2009). This is unfortunate because ISC may affect fundamental evolutionary processes such as adaptation (Rice 1992) and speciation (Rice & Chippindale 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Work, largely with Drosophila, suggests that such intralocus sexual conflict occurs widely throughout the genome [151][152][153][154][155][156]. Although some intralocus sexual conflict can be resolved by sex specific expression and genomic imprinting [56], a growing body of work suggests that intralocus sexual conflict is common and occurs at all stages of an organisms development [154], and can have implications for many areas of sexual selection [155,156], including sperm competition.…”
Section: Conflict Between Sperm (Haploid) and Male (Diploid) Phasesmentioning
confidence: 99%